2021
DOI: 10.5796/electrochemistry.21-00038
|View full text |Cite
|
Sign up to set email alerts
|

Revisiting Delithiated Li<sub>1.2</sub>Mn<sub>0.54</sub>Ni<sub>0.13</sub>Co<sub>0.13</sub>O<sub>2</sub>: Structural Analysis and Cathode Properties in Magnesium Rechargeable Battery Applications

Abstract: Chemically-delithiated Li 1.2 Mn 0.54 Ni 0.13 Co 0.13 O 2 is regarded as a potential candidate of cathode active materials for magnesium rechargeable batteries owing to its large deliverable capacity and high operation voltage compared to conventional layered transition metal oxides. Our previous study suggested its chemical composition as Li 0.13 Mn 0.54 Ni 0.13 Co 0.13 O 2−δ by X-ray diffraction combined with XAFS analysis. We herein re-analyzed the substantial composition and crystal structure by employing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…Ishida et al used the chemical delithiation method to exploit delithiated lithium‐rich Li 1.2 Mn 0.54 Ni 0.13 Co 0.13 O 2 as a Mg 2+ intercalation material in magnesium rechargeable battery applications. [ 92 ] Delithiation of LiFePO 4 with Br 2 and NO 2 BF 4 has been performed for the use of heterosite FePO 4 as sodium intercalation material. [ 93,94 ] Subsequent sodiation can be performed in a Na–metal/FePO 4 cell, or by chemical sodiation with NaI.…”
Section: Applicationsmentioning
confidence: 99%
“…Ishida et al used the chemical delithiation method to exploit delithiated lithium‐rich Li 1.2 Mn 0.54 Ni 0.13 Co 0.13 O 2 as a Mg 2+ intercalation material in magnesium rechargeable battery applications. [ 92 ] Delithiation of LiFePO 4 with Br 2 and NO 2 BF 4 has been performed for the use of heterosite FePO 4 as sodium intercalation material. [ 93,94 ] Subsequent sodiation can be performed in a Na–metal/FePO 4 cell, or by chemical sodiation with NaI.…”
Section: Applicationsmentioning
confidence: 99%
“…The combination of a highly efficient and electrochemically stable electrolyte and ZnMnO 3 nanoparticles with shortened diffusion pathways has been reported to result in stable battery cycling even at 30 °C . In addition to the spinel-type cathode materials, various other cathode materials have been developed, including stoichiometric MgFePO 4 F, vanadium phosphate V 2 (PO 4 ) 3 , rocksalt-structured Mg x Ni y Co z O 2 ( x + y + z ≤ 2.0), a Li + -ion cathode material chemically desorbed from Li, and ion-exchanged MgFeSiO 4 . Furthermore, numerous studies of rechargeable battery materials have been conducted using first-principles calculations and molecular dynamics simulations. Ceder et al showed that the performance of Li-rich cationic anisotropic rocksalt cathodes is improved by Mg-substitution …”
Section: Introductionmentioning
confidence: 99%
“…[2][3][4][5][6] However, the researches on the Li2MnO3-based systems have revealed that anionic redox triggers partial oxygen loss and subsequent irreversible phase transition, resulting in voltage decay on continuous cycles and restricting its use for practical battery applications. 7,8 Recently, our group has reported that the x Li3NbO4 − (1−x) LiVO2 binary system can be used for high-capacity positive electrode materials without anionic redox involvement. 9,10 Unlike Li2MnO3-based systems, better capacity retention is achieved in Li-excess vanadium-based oxides, Li1.25Nb0.25V0.5O2 (x = 0.33 in x Li3NbO4 − (1−x) LiVO2), with two-electron cationic redox of V 3+ /V 5+ .…”
Section: Introductionmentioning
confidence: 99%